Portable electronic tongue based on screen-printed electrodes coupled with chemometrics for rapid differentiation of Brazilian lager beer. (September 2021) - Mutz, Yhan S.; Rosario, Denes do; Silva, Luiz R.G.; Santos, Francine D.; Santos, Layla P.; Janegitz, Bruno C.; Filgueiras, Paulo R.; Romão, Wanderson; de Q Ferreira, Rafael; Conte-Junior, Carlos A.
Abstract: Quality and authenticity monitoring are activities of growing necessity worldwide. However, methods of rapid evaluation and low cost need to be further explored to intensify and optimize the monitoring process. Hence, the present study proposes a procedure for discrimination of lager beers (premium and standard American lager beers) using commercially available screen-printed electrodes (SPEs) (carbon (SPCE), gold (SPGE), and carbon nanotube (SPEs-CNT)) and chemometric classification methods (soft independent modeling of class analogy (SIMCA) and partial least squares regression discriminant analysis (PLS-DA)). Overall, PLS-DA models obtained, on average, 88% for sensitivity, specificity, and precision in the validation dataset. The SIMCA models, on the other hand, showed, on average, 72% of sensitivity, 82% specificity and 80% of precision. The electronic tongue's final configuration of an SPCE coupled with PLS-DA showed a predictive power of 94%, using only one SPCE with the capacity of analyze up to 35 beers per SPEs. Graphical abstract: Image 1 Highlights: Differentiation of Brazilian beers based on electrochemical measures. Simple, fast, and very low reagent consumption (μL) electroanalytical method. Portable equipment associated with disposable commercially available electrode. Electronic tongue composed of a carbon screen printed electrode and PLS-DA. Discriminant analysis (PLS-DA) lead to a 94% correct discrimination of beers.